The use of Design Thinking in creating projects and improving customer value perception: an experience report on software projects at a Research and Development Institute in Amazonas - Lobão, Luana; Rabaioli, Brunna Talita Vieira; Gauthier, Elizabeth; Araújo, Lívia Lobão De; Meireles, Maria Alcimar Costa (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2023: Anais do XXII Simpósio Brasileiro de Qualidade de Software, 2023)
Context:The measure of success for a product is the extent to which it meets users’ needs. To meet these needs, it’s necessary to understand what they are. In this context, where the user and their needs are central to the success of a product, Design Thinking (DT) techniques are essential. Objective: This study presents the application of Design Thinking techniques in innovation projects at a significant Research and Development Institute in Manaus, aiming to enhance customer value perception and satisfaction with the deliverables. Method: The research strategy employed in this study was field research, the methods were exploratory case study and archival research, with quantitative and qualitative analyses conducted on the data. Results: It was possible to notice that there was an increase in customer satisfaction indicators through the utilization of Design Thinking (DT) techniques in the process of uncovering user needs. The CVP (Customer Value Perception), which assesses customer satisfaction concerning intermediate project deliverables, rose from 3.3 in 2016 to 4.0 in 2022, where score 1 represents the minimum and 5 the maximum rating. The NPS (Net Promoter Score), gauging customer value perception across all organization sectors, surged from -50 (Critical Zone) in 2016 to 71.4 (Quality Zone) in 2022, with -100 as the lowest and 100 as the highest achievable score. These data were collected considering the CVP and NPS surveys conducted between 2016 and 2022. Conclusion: The results demonstrate that implementing DT techniques assisted the Institute in achieving greater precision in its deliverables. In response to this insight, the Institute has established a laboratory to facilitate collaborative meetings and co-creation sessions to enhance customer engagement and foster project innovation.